Letter to Jane Tolmach from Governor Edmund G. Brown Jr. 1980 - Edmund G. Brown Jr.:::::: (1980)
A letter to Jane Tolmach informing her she has been sent an advance copy of a booklet prepared by the Office of Planning and Research in California.